3.4: Applications of TFE mask‐less technology for foldable AMOLED displays. (4th October 2019) - Guo, Linshan; Lee, HeeYol; Shen, Peng; Rao, Yuanyuan; Cai, Yu; Huang, Dan; Yan, Jun; Li, Jiaxin; Wang, Junqiang; Cao, Zhonghuan; Feng, Zaiwu
Abstract : Thin‐film encapsulation (TFE) for foldable AMOLED display is necessary to have good reliability and excellent bendability. TFE mask induces particles easily and crack occurs in thick TFE layer during panel bending. We developed TFE with Al2 O3 layer for high water‐proof and very thin thickness, satisfying the requirement of reliability and bendability. The Al2 O3 layer in TFE structure was deposited by low temperature atomic layer deposition (ALD) method, and we realized TFE mask‐less process through adapting dry‐etch parameters for Al2 O3 etch, finding that BCl3 has very excellent dry‐etch selectivity between inorganic layer (SiOx/SiNx/SiOxNy) and Al2 O3 . Besides, we also attempted to make the organic layer of TFE acted as etch mask, and it proved to be feasible, indicating that all the TFE masks could be taken out effectively. Moreover, we proved good optic and reliability characteristics of AMOLED display with mask‐less TFE structure.